The effect of deformability on the microscale flow behavior of red blood cell suspensions - Passos, Andreas; Sherwood, Joseph M.; Kaliviotis, Efstathios; Agrawal, R.; Pavesio, C.; Balabani, Stavroula (My University, 2019)
Red blood cell (RBC) deformability is important for tissue perfusion and a key determinant of blood rheology. Diseases such as diabetes, sickle cell anemia, and malaria, as well as prolonged storage, may affect the mechanical properties of RBCs altering their hemodynamic behavior and leading to microvascular complications. However, the exact role of RBC deformability on microscale blood flow is not fully understood. In the present study, we extend our previous work on healthy RBC flows in bifurcating microchannels [Sherwood et al., “Viscosity and velocity distributions of aggregating and non-aggregating blood in a bifurcating microchannel,” Biomech. Model. Mechanobiol. 13, 259–273 (2014); Sherwood et al., “Spatial distributions of red blood cells significantly alter local hemodynamics,” PLoS One 9, e100473 (2014); and Kaliviotis et al., “Local viscosity distribution in bifurcating microfluidic blood flows,” Phys. Fluids 30, 030706 (2018)] to quantify the effects of impaired RBC deformability on the velocity and hematocrit distributions in microscale blood flows. Suspensions of healthy and glutaraldehyde hardened RBCs perfused through straight microchannels at various hematocrits and flow rates were imaged, and velocity and hematocrit distributions were determined simultaneously using micro-Particle Image Velocimetry and light transmission methods, respectively. At low feed hematocrits, hardened RBCs were more dispersed compared to healthy ones, consistent with decreased migration of stiffer cells. At high hematocrit, the loss of deformability was found to decrease the bluntness of velocity profiles, implying a reduction in shear thinning behavior. The hematocrit bluntness also decreased with hardening of the cells, implying an inversion of the correlation between velocity and hematocrit bluntness with loss of deformability. The study illustrates the complex interplay of various mechanisms affecting confined RBC suspension flows and the impact of both deformability and feed hematocrit on the resulting microstructure.
Keywords: Blood; Cytology; Cells RBCs